EGFR Inhibitors: Current Status, Resistance Mechanisms, and Market Insight - Magar, Vidya Kishanrao; Khavane, Karna Bhagwanrao (Indian Journal of Pharmacy Practice)
The Epidermal Growth Factor Receptor (EGFR) is a pivotal oncogenic driver in Non-Small Cell Lung Cancer (NSCLC) and other epithelial malignancies. Over the past two decades, successive generations of EGFR Tyrosine Kinase Inhibitors (TKIs) have transformed the therapeutic landscape, beginning with reversible first-generation agents like gefitinib and erlotinib, progressing to irreversible second-generation TKIs such as afatinib, and culminating in third-generation agents like osimertinib, designed to overcome T790M-mediated resistance. However, despite initial efficacy, therapeutic resistance invariably emerges—most notably via the EGFR C797S mutation or through bypass mechanisms including MET amplification, HER2 activation, histologic transformation, and downstream pathway mutations (e.g., PIK3CA, KRAS). Fourth-generation EGFR inhibitors—comprising allosteric and non-covalent ATP-competitive agents—are now in early clinical evaluation to target triple-mutant EGFR (L858R/T790M/C797S) tumors. The EGFR-targeted therapy market, valued at USD 9-10 billion in 2023, is projected to exceed USD 15 billion by 2032, driven by drug innovation, expanded access to molecular diagnostics, and rising EGFR mutation prevalence, particularly in Asia-Pacific. Furthermore, novel therapeutic modalities such as bispecific antibodies (e.g., amivantamab), antibody-drug conjugates, and AI-driven resistance prediction models are redefining treatment personalization. This review provides a comprehensive analysis of the mechanistic evolution of EGFR inhibitors, resistance landscapes beyond C797S, emerging fourth-generation strategies, and market dynamics—highlighting future directions in precision oncology.
Keywords: EGFR inhibitors; Non-small cell lung cancer; Resistance mechanisms; C797S mutation; Targeted therapy; Fourth-generation TKIs; Market trends; Precision oncology